Development of mobile application of non resident students of UiTM Perlis / Aina Liyana Mohamad Zamri - Mohamad Zamri, Aina Liyana (2019)
The student who lived outside the campus was known as Non-Resident or off-campus student. Non-Resident student usually rent homes in the residential area near the campus such as apartments, terraces and others. Mobile application of Non-Resident student of UiTM Perlis aims to utilize the GIS application in mobile application development of NR student of UiTM Perlis. The objectives of this project was to create NR students database, to develop mobile application of NR student of UiTM Perlis and lastly to test the prototype to the staff of UiTM Perlis. It specifically studies on residential area near UiTM Perlis. This research is based on data obtained from Non-Resident Students Management Unit in UiTM Perlis. The data then was used to identify the location of Non-Resident student's rental house. The data was presented in ArcGIS Online as an interactive map that the user can view and access the actual location of student's rental house. The results of the study is the mobile application that can view the actual location and information of the Non-Resident student.